Commodity Asian option pricing and simulation in a 4-factor model with jump clusters - Riccardo Brignone; Luca Gonzato; Carlo Sgarra (Annals of Operations Research, 2023)
Mean reversion, stochastic volatility, convenience yield and presence of jump clustering are well documented salient features of commodity markets, where Asian options are very popular. We propose a model which takes into account all these stylized features. We first state our model under the historical measure, then, after introducing a structure preserving change of measure, we provide a risk-neutral version of the same model and we show how to price geometric and arithmetic Asian options. To this end, we derive semi-closed formulas for the geometric Asian options price and develop a computationally efficient simulation scheme for the price process, allowing to price the arithmetic counterparts using control variate technique. Finally, we propose a simple econometric experiment to document presence of jump clusters in commodity prices and evaluate the performances of the proposed simulation scheme on some parameter sets calibrated on real data.
Keywords: C15; C63; G13; Q02; 000; Commodity derivatives; Multifactor affine stochastic volatility models; Self-exciting jumps; Simulation; Asian options